Analysis of Regional Government Financial Performance Based on Value for Money: JEL Classification: H72; H83; H61; M41; O18 - Kinan Nabawi; Fahmi Aziz; Muhammad Nizar Alif; Nur Maia Sella (Mustard Journal De Ecobusin, 2026)
This study examines regional government financial performance through the application of the value for money framework, which emphasizes the dimensions of economy, efficiency, and effectiveness in public sector financial management. Using a quantitative descriptive–analytical design, the study relies on secondary data obtained from audited regional government financial statements, budget realization reports, and official performance documents. The analysis focuses on regional governments operating within a decentralized fiscal system, enabling an evaluation of how public funds are planned, allocated, and utilized to achieve policy objectives. The findings indicate that regional governments generally demonstrate strong economy performance, as reflected in realized expenditures that are largely below or close to approved budget allocations, suggesting effective cost control and fiscal discipline. However, efficiency and effectiveness results vary considerably across regions and fiscal periods, revealing that prudent spending alone does not guarantee optimal resource utilization or successful achievement of targeted outcomes. Several regions with high budget absorption levels exhibit moderate or low efficiency and effectiveness, indicating gaps between financial inputs, outputs, and outcomes. These results confirm that financial performance in the public sector is multidimensional and cannot be adequately assessed using budget realization indicators alone. The study concludes that the value for money framework provides a comprehensive and practical tool for evaluating regional government performance, supporting accountability, and informing performance-oriented public financial management reforms.